Role of the bed nucleus of the stria terminalis in feeding - Wang, Keyan; Guo, Wenbo; Xu, Jiaxiang; Kuang, Yingjie; Chen, Xiqi (Frontiers in Nutrition, 2025)
As an important part of the limbic system of the forebrain, the bed nucleus of the stria terminalis (BNST) plays a key role in stress response, emotion regulation, and motivational behavior. Recent studies have demonstrated that BNST plays a crucial role in the pathological process of appetite regulation, food selection, and eating disorders by integrating metabolic signals, reward feedback, and stress input. This article systematically reviews the anatomical subdivision, neural loop characteristics, and multimodal mechanisms of the BNST in food intake regulation; discusses its association with obesity, anorexia nervosa, and other diseases; and explores potential therapeutic strategies targeting the BNST.